2021
DOI: 10.1177/23328584211052050
|View full text |Cite
|
Sign up to set email alerts
|

Distance Teaching During the COVID-19 Crisis: Social Connectedness Matters Most for Teaching Quality and Students’ Learning

Abstract: In spring 2020, school closures were enacted to slow the spread of the COVID-19 pandemic. Students and teachers faced the challenge of organizing digital teaching and learning without sufficient time to prepare. In this study, we investigated how teachers implemented teaching from a distance and how these different implementations were associated with students’ and parents’ perceptions of teaching quality and students’ social involvement, enjoyment of learning, academic effort, and perceived competence. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…Klieme (2020), Voss and Wittwer (2020), and Meyer (2020) argued on the basis of theoretical considerations that the three constructs of instructional quality also represent important aspects of high-quality in distance education. Initial empirical work on distance education (Frohn, 2022;Jaekel et al, 2021;Steinmayr et al, 2021) supports these assumptions with both quantitative and qualitative data. For instance, Jaekel et al (2021) found that teaching methods enabling social connectedness revealed positive associations with students' and parents' ratings of instructional quality and students' learning experiences during distance learning.…”
Section: Instructional Quality Of Distance Educationmentioning
confidence: 92%
See 2 more Smart Citations
“…Klieme (2020), Voss and Wittwer (2020), and Meyer (2020) argued on the basis of theoretical considerations that the three constructs of instructional quality also represent important aspects of high-quality in distance education. Initial empirical work on distance education (Frohn, 2022;Jaekel et al, 2021;Steinmayr et al, 2021) supports these assumptions with both quantitative and qualitative data. For instance, Jaekel et al (2021) found that teaching methods enabling social connectedness revealed positive associations with students' and parents' ratings of instructional quality and students' learning experiences during distance learning.…”
Section: Instructional Quality Of Distance Educationmentioning
confidence: 92%
“…Initial empirical work on distance education (Frohn, 2022;Jaekel et al, 2021;Steinmayr et al, 2021) supports these assumptions with both quantitative and qualitative data. For instance, Jaekel et al (2021) found that teaching methods enabling social connectedness revealed positive associations with students' and parents' ratings of instructional quality and students' learning experiences during distance learning. Finally, Steinmayr et al (2021) found that distance teaching activities that corresponded with dimensions of teaching quality (e.g., feedback, teacher-child-communication) were comparatively strongly correlated with students' motivation and learning progress during the school lockdown for both elementary and secondary school students.…”
Section: Instructional Quality Of Distance Educationmentioning
confidence: 92%
See 1 more Smart Citation
“…Helm et al [35] have found that the quality of learning and teaching during remote learning is largely dependent on the performance of individual teachers, because a schoolwide conceptualization of distance education was often lacking, due to the suddenness of the school closures. Jaekel et al [36] have suggested that interactive student-teacher and student-student connectedness is most important for instructional quality and student learning in remote learning. Online group work can create an interactive social group context, which is otherwise compromised by social distancing.…”
Section: The Covid-19 Pandemic and Remote Learningmentioning
confidence: 99%
“…Then it matters whether the teacher uses the lecture format or the student-centered instruction. However, organizing the lessons in this way does not mean that student outcomes will be predicted correctly (Jaekel et al, 2021).…”
Section: Teaching Qualitymentioning
confidence: 99%